2020
DOI: 10.1038/s42003-020-01165-z
|View full text |Cite
|
Sign up to set email alerts
|

2-Nitroimidazoles induce mitochondrial stress and ferroptosis in glioma stem cells residing in a hypoxic niche

Abstract: Under hypoxic conditions, nitroimidazoles can replace oxygen as electron acceptors, thereby enhancing the effects of radiation on malignant cells. These compounds also accumulate in hypoxic cells, where they can act as cytotoxins or imaging agents. However, whether these effects apply to cancer stem cells has not been sufficiently explored. Here we show that the 2-nitroimidazole doranidazole potentiates radiation-induced DNA damage in hypoxic glioma stem cells (GSCs) and confers a significant survival benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…The effect of radiation exposure on prostate cancer cells was analyzed as previously described 12 . X-ray irradiation was delivered using an MBR-1520R-4 system (Hitachi Power Solutions, Ibaraki, Japan) at settings of 150 kV and 20 mA.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of radiation exposure on prostate cancer cells was analyzed as previously described 12 . X-ray irradiation was delivered using an MBR-1520R-4 system (Hitachi Power Solutions, Ibaraki, Japan) at settings of 150 kV and 20 mA.…”
Section: Methodsmentioning
confidence: 99%
“…In colorectal CSCs, knockdown or inhibition of SLC7A11 significantly and specifically kills cancer cells and thus attenuates chemoresistance in CRC ( Xu et al, 2020c ). Besides, two nitroimidazoles ( Koike et al, 2020 ), itraconazole ( Xu et al, 2021 ), and dichloroacetate ( Sun et al, 2021 ) are also proven to have therapeutic potential through promoting ferroptosis in CSCs.…”
Section: Ferroptosis and Cancer Stem Cellsmentioning
confidence: 99%
“…We found this glucose concentration to be 0.175 mM, which corresponds to 1% of the concentration in our standard culture condition. We have previously shown that GSCs can differ in their main energy pathway, and have established two clonal GSC populations, glycolytic GSCs (GSC gly , line GSCA), and oxidative GSCs (GSC mit , line GSCB) [ 12 ], as well as a non-clonal population containing predominantly oxidative GSCs (TSH) [ 12 , 24 ]. Here, we first cultured GSCA and GSCB in in a medium containing 0.175 mM glucose (ultralow glucose medium, or ULGM) and various concentrations of lactate ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…The GSCs used in our study were established by transformation of neural stem/progenitor cells with the oncoprotein H-Ras V12 [ 12 , 24 , 30 ]. Given that neuronal stem cells are able to survive on lactate for up to 24 h [ 22 ], the ability of GSCs to use lactate might reflect a characteristic of their cell of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation